ARTI PENTING DELIMITASI PERAIRAN PEDALAMAN SETIAP PULAU DI INDONESIA - Maria Maya Lestari (Legality : Jurnal Ilmiah Hukum, 2017)
Maritime zones of the sovereignty of the Indonesian archipelago can be divided into inland waters, archipelagic waters and territorial sea. But only in the inland waters of Indonesia have absolute sovereignty without any other state right. In order to guarantee and maintain the sovereignty of the country in the inland water zone from overlapping interests and rights of other countries in the zone of Indonesian maritime sovereignty, Indonesia should immediately establish the limits of delimitation of the inland waters and establish legislation to prevent violations of the sovereignty of Indonesia's inland waters territory by the state other. Delimitation of each islands is considered very important in order to maintain the security and defense of the country. The government must immediately establish inland water areas and ports considered strategic and vital to the defense and security of the country. Areas that are considered important this can be closing and banning to enter and / or stopover. So our marine law is firm and we can become a sovereign country in the sea region.